Cover Feature: Direct Measurements of the Cobalt‐Thiolate Bonds Strength in Rubredoxin by Single‐Molecule Force Spectroscopy (ChemBioChem 12/2022). (24th May 2022) - Shi, Shengchao; Wu, Tao; Zheng, Peng
Abstract : Single‐molecule force spectroscopy is a powerful tool which can quantify the strength of the metal–ligand bond. In this study, the strength of cobalt–thiolate bonds in Co‐substituted rubredoxin was measured for the first time. The polymerized rubredoxin with cobalt ion ready for single‐molecule measurement was constructed by combination of classic chemical denature/renature and cysteine coupling methods. More information can be found in the Research Article by P. Zheng et al.